Post-steroid panniculitis in an adult - Marovt, Maruška (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2012)
Post-steroid panniculitis is an extremely rare phenomenom caused by inappropriate interruption of long-term systemic corticosteroid therapy. It usually occurs in children and is characterized by development of multiple subcutaneous nodules on the cheeks, arms, and trunk. Histologically it is a lobular type of panniculitis with characteristic needle-shaped clefts within adipocytes and numerous foreign-body giant cells. We present a case of post-steroid panniculitis in a 50-year-old female after long-term administration of oral corticosteroids for Sjögren's syndrome accompanied by leukocytoclastic vasculitis and chronic polyarthritis.
Keywords: drug; kortikosteroidi; kožne bolezni; odrasli; panikulitis; stranski učinki; zdravila